Basalt fiber composite core overhead conductor and process for producing same
Patent Information
- Application Number
- CN202611322737.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]本发明旨在解决上述现有技术中存在的玄武岩纤维与树脂基体界面结合力弱、复合材料力学性能不足以及浸渍工艺缺陷等技术问题,提供一种玄武岩纤维复合材料芯架空导线,包括:由多根玄武岩纤维单丝集束而成的纤维束,以及浸渍并固化于所述纤维束内部及表面的树脂基体;所述玄武岩纤维单丝表面具有改性涂层,所述树脂基体为经增韧和纳米增强的改性热固性树脂体系
本发明通过多尺度、多组分的协同改性策略,取得了以下显著有益效果:第一,通过纳米纤维素晶须与环氧官能化聚苯胺衍生物复合上浆剂对玄武岩纤维进行表面改性,纳米纤维素晶须在纤维表面形成纳米尺度的粗糙结构增加物理锚固效应,其表面的羟基与纤维表面的硅羟基形成氢键结合,同时环氧官能化聚苯胺衍生物的环氧基团可与树脂基体中的固化剂或环氧基团发生共聚反应,在纤维与基体之间形成化学键合,二者协同作用使纤维/树脂界面剪切强度提升80%以上,有效解决了玄武岩纤维表面惰性导致的界面结合力弱的问题。第二,通过环氧化聚丁二烯橡胶与POSS纳米粒子对环氧树脂进行协同增韧增强,橡胶相的弹性体特性赋予基体良好的韧性,断裂韧性提升120%以上,而POSS纳米粒子的刚性硅氧笼状骨架有效补偿了橡胶增韧带来的模量损失,使复合材料在保持较高弯曲模量的同时获得优异的抗冲击性能,克服了增韧与耐热性、模量相互制约的行业技术难题。第三,超临界二氧化碳辅助浸渍工艺利用其超强的渗透能力和零表面张力特性,使树脂能够充分浸润纤维束内部每一根单丝的间隙,将复合材料内部孔隙率由常规工艺的3%~5%降低至0.5%以下,显著改善了材料的长期耐老化性能和疲劳寿命。第四,非等温梯度固化工艺通过低温预固化、中温固化和高温后固化三个阶段精确控制交联反应进程,有效消除了制品内部的热应力和收缩应力,制品尺寸稳定性和力学可靠性的批次一致性显著提高。最终产品在拉伸强度、弯曲模量、断裂韧性及湿热老化强度保留率等关键指标上均取得显著进步,实现了低成本玄武岩纤维复合材料芯架空导线的高性能化,具有良好的市场应用前景和产业化推广价值。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention provides an overhead conductor with a basalt fiber composite core and its manufacturing process, belonging to the technical field of overhead power transmission conductors. Background Technology
[0002] Carbon fiber composite conductors have been increasingly widely used in overhead transmission lines due to their high strength, low sag, and high temperature resistance. However, the high cost of carbon fiber severely restricts its widespread adoption in large-scale power transmission projects. Basalt fiber, made from melt-drawn natural basalt ore, is widely available, inexpensive, and possesses excellent corrosion resistance, high temperature resistance, and good insulation properties, making it an ideal candidate material to replace carbon fiber as a composite core reinforcement. However, basalt fiber faces a series of key technical bottlenecks in practical applications. First, the smooth and chemically inert surface of basalt fiber lacks active functional groups that can form strong chemical bonds with the resin matrix, resulting in weak interfacial bonding between the fiber and thermosetting matrices such as epoxy resin, preventing effective load transfer from the matrix to the fiber reinforcement. Second, the tensile modulus of basalt fiber (approximately 80–95 GPa) is significantly lower than that of carbon fiber (approximately 230 GPa). Directly replacing carbon fiber as a reinforcement leads to a significant decrease in the overall tensile strength, bending resistance, and fatigue resistance of the composite core. Third, in existing conventional resin impregnation processes, high-viscosity epoxy resins struggle to fully penetrate the micro- and nano-pores between the individual filaments within the fiber bundle, resulting in high porosity in the composite material. These pores become stress concentration sources and triggering points for aging failure during service. Furthermore, the epoxy resin matrix itself is quite brittle, and toughening modifications often come at the cost of sacrificing heat resistance and modulus. The contradiction between toughening, heat resistance, and reinforcement has long been a technical challenge that the industry has struggled to overcome effectively. Therefore, how to fully utilize the cost advantages of basalt fibers while synergistically improving the comprehensive mechanical properties of basalt composites through material modification and process innovation, to achieve or approach the performance level of carbon fiber composites, is a key technical problem urgently needing to be solved in this field. Summary of the Invention
[0003] This invention aims to solve the technical problems existing in the prior art, such as weak interfacial bonding between basalt fiber and resin matrix, insufficient mechanical properties of composite materials, and defects in impregnation process. It provides a basalt fiber composite core overhead conductor, comprising: a fiber bundle formed by multiple basalt fiber monofilaments, and a resin matrix impregnated and cured inside and on the surface of the fiber bundle; the surface of the basalt fiber monofilaments has a modified coating, and the resin matrix is a modified thermosetting resin system that has been toughened and nano-reinforced.
[0004] Preferably, the modified coating is a composite sizing agent coating comprising nanocellulose whiskers and a conductive polymer derivative; the conductive polymer derivative is a polyaniline derivative with epoxy functional groups; the mass ratio of nanocellulose whiskers to the polyaniline derivative with epoxy functional groups in the composite sizing agent coating is 1:3 to 1:8; the nanocellulose whiskers are sulfonated cellulose nanowhiskers with a diameter of 5-10 nm and an aspect ratio of 10-20; the polyaniline derivative with epoxy functional groups is a copolymer of N-glycidyl aniline and aniline, wherein the molar percentage of N-glycidyl aniline is 5%-15%.
[0005] Preferably, the resin matrix comprises a base epoxy resin, a toughening modifier, and nano-reinforcing particles; the toughening modifier is a block copolymer rubber, and the nano-reinforcing particles are polyhedral oligomeric silsesquioxanes; the base epoxy resin is a bisphenol A type epoxy resin or a bisphenol F type epoxy resin, with an epoxy equivalent of 170–210 g / eq; the block copolymer rubber is epoxidized polybutadiene rubber, with an epoxidation degree of 20%–60%, a number average molecular weight of 2000–8000, and a mass fraction of 5%–20% in the resin matrix; the polyhedral oligomeric silsesquioxane is a polyhedral oligomeric silsesquioxane with epoxy groups, and a mass fraction of 1%–8% in the resin matrix; the mass ratio of the base epoxy resin, epoxidized polybutadiene rubber, and polyhedral oligomeric silsesquioxane in the resin matrix is 100:(5–20):(1–8).
[0006] Preferably, a gradient interface layer is formed between the fiber bundle and the resin matrix, and the modulus of the gradient interface layer decreases from the inside to the outside along the radial direction of the fiber; the thickness of the gradient interface layer is 50-200 nm; the diameter of the basalt fiber monofilaments in the fiber bundle is 7-20 μm, the linear density of the fiber bundle is 600-4800 tex, and the number of monofilaments in the fiber bundle is 50-400.
[0007] Preferably, the fiber volume fraction in the composite core is 50%–75%, the resin matrix volume fraction is 25%–50%, and the diameter of the composite core is 2–15 mm.
[0008] The present invention also provides a production process for the above-mentioned basalt fiber composite core overhead conductor, comprising the following steps: surface modification treatment of basalt fibers to obtain fiber bundles with modified coatings; impregnation and compounding of the modified fiber bundles with a liquid resin matrix under the assistance of supercritical fluid to obtain a prepreg; and non-isothermal gradient curing treatment of the prepreg to obtain the composite core.
[0009] Preferably, the surface modification treatment includes plasma pretreatment and sizing agent coating; the plasma pretreatment atmosphere is argon or nitrogen, the treatment power is 100-500W, the treatment time is 1-10min, and the gas flow rate is 50-200sccm; the sizing agent coating uses a composite emulsion containing nano-cellulose whiskers and polyaniline derivatives with epoxy functional groups; the solid content of the composite emulsion is 1%-5%, and the mass ratio of nano-cellulose whiskers to polyaniline derivatives with epoxy functional groups is 1:3 to 1:8; the sizing agent coating uses an impregnation method, the impregnation time is 5-30min, the impregnation temperature is 20-40℃, and after coating, it is dried at 80-120℃ for 10-60min.
[0010] Preferably, the supercritical fluid is supercritical carbon dioxide; the impregnation and composite temperature is 40–80°C, the pressure is 8–15 MPa, the processing time is 10–60 min; and the flow rate of supercritical carbon dioxide is 5–50 L / min.
[0011] Preferably, the non-isothermal gradient curing process includes a low-temperature pre-curing stage, a medium-temperature curing stage, and a high-temperature post-curing stage performed sequentially; the temperature of the low-temperature pre-curing stage is 80–120°C, and the time is 30–120 min; the temperature of the medium-temperature curing stage is 130–170°C, and the time is 60–180 min; the temperature of the high-temperature post-curing stage is 180–220°C, and the time is 30–90 min; the heating rate from the low-temperature pre-curing stage to the medium-temperature curing stage is 1–5°C / min, and the heating rate from the medium-temperature curing stage to the high-temperature post-curing stage is 0.5–3°C / min.
[0012] Preferably, the resin matrix is pre-prepared before impregnation and lamination, specifically by: heating the base epoxy resin to 50-80°C, adding epoxidized polybutadiene rubber and stirring for 10-60 minutes, adding polyhedral oligomeric silsesquioxane and continuing to stir for 10-30 minutes, adding a curing agent and an accelerator, stirring and mixing evenly, and then vacuum degassing for 10-30 minutes; the curing agent is an anhydride-based curing agent or an amine-based curing agent, and the amount of curing agent is 50%-1% of the mass of the epoxy resin. 00%; the accelerator is a tertiary amine accelerator or an imidazole accelerator, and the amount of accelerator is 0.5% to 5% of the epoxy resin mass; the anhydride curing agent is methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride or nadic anhydride; the amine curing agent is 4,4′-diaminodiphenylmethane, 4,4′-diaminodiphenyl sulfone or m-phenylenediamine; the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol, N,N-dimethylbenzylamine or 2-ethyl-4-methylimidazole.
[0013] Preferably, the surface modification treatment further includes a fiber preheating treatment step: heat-treating the basalt fiber at 200-400℃ for 10-60 minutes to remove the sizing agent and impurities from the fiber surface.
[0014] The beneficial effects of this invention are as follows: This invention achieves the following significant beneficial effects through a multi-scale, multi-component synergistic modification strategy: First, by using a composite sizing agent of nanocellulose whiskers and epoxy-functionalized polyaniline derivatives to modify the surface of basalt fibers, the nanocellulose whiskers form a nanoscale rough structure on the fiber surface, increasing the physical anchoring effect. The hydroxyl groups on their surface form hydrogen bonds with the silanol groups on the fiber surface. At the same time, the epoxy groups of the epoxy-functionalized polyaniline derivatives can undergo copolymerization reactions with the curing agent or epoxy groups in the resin matrix, forming chemical bonds between the fiber and the matrix. The synergistic effect of the two increases the shear strength of the fiber / resin interface by more than 80%, effectively solving the problem of weak interfacial bonding caused by the surface inertness of basalt fibers. Second, the epoxy resin is synergistically toughened and reinforced by epoxidized polybutadiene rubber and POSS nanoparticles. The elastomeric properties of the rubber phase endow the matrix with good toughness, increasing fracture toughness by more than 120%. Meanwhile, the rigid silica cage-like skeleton of the POSS nanoparticles effectively compensates for the modulus loss caused by rubber toughening, enabling the composite material to achieve excellent impact resistance while maintaining a high flexural modulus, overcoming the industry's technical challenge of mutual constraints between toughening, heat resistance, and modulus. Third, the supercritical carbon dioxide-assisted impregnation process utilizes its strong penetration ability and zero surface tension characteristics to allow the resin to fully wet the gaps between each filament inside the fiber bundle, reducing the internal porosity of the composite material from 3%–5% in conventional processes to below 0.5%, significantly improving the material's long-term aging resistance and fatigue life. Fourth, the non-isothermal gradient curing process precisely controls the crosslinking reaction process through three stages: low-temperature pre-curing, medium-temperature curing, and high-temperature post-curing, effectively eliminating thermal stress and shrinkage stress inside the product, and significantly improving the batch consistency of product dimensional stability and mechanical reliability. The final product has made significant progress in key indicators such as tensile strength, flexural modulus, fracture toughness and strength retention rate under damp heat aging, realizing the high performance of low-cost basalt fiber composite core overhead conductors, and has good market application prospects and industrialization promotion value. Detailed Implementation
[0015] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0016] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to this invention. The preferred embodiments and materials described herein are for illustrative purposes only and do not limit the scope of this application.
[0017] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the experimental materials used in the following examples are all purchased from commercial channels.
[0018] The raw materials used in the following examples and comparative examples and their sources are as follows: basalt fiber continuous untwisted roving (linear density 2400 tex, monofilament diameter 13 μm, Zhejiang Shijin Basalt Fiber Co., Ltd.); bisphenol A type epoxy resin E51 (epoxy equivalent 185-210 g / eq, Nantong Xingchen Synthetic Materials Co., Ltd.); bisphenol F type epoxy resin NPEF-170 (epoxy equivalent 160-180 g / eq, Nanya Epoxy Resin Co., Ltd.); methyltetrahydrophthalic anhydride (curing agent, Puyang Huicheng Electronic Materials Co., Ltd.); 4,4′-diaminodiphenyl sulfone (curing agent, ... Sigma-Aldrich); 2-Ethyl-4-methylimidazolium (accelerator, Shanghai Aladdin Biochemical Technology Co., Ltd.); 2,4,6-Tris(dimethylaminomethyl)phenol (accelerator, Shanghai Maclean Biochemical Technology Co., Ltd.); Epoxidized polybutadiene rubber (epoxidation degree 35%, number average molecular weight 5000, Lanxess Chemical, Germany); Epoxidized polybutadiene rubber (epoxidation degree 50%, number average molecular weight 3000, Nippon Soda Co., Ltd.); Glycidyl-based POSS (polyhedral oligomeric silsesquioxane, epoxy equivalent approximately 150 g / eq, Hybrid, USA). Plastics Corporation); sulfonated cellulose nanofibers (5-10 nm in diameter, aspect ratio 10-20, Guilin Qihong Technology Co., Ltd.); N-glycidyl aniline (Shanghai Haohong Biomedical Technology Co., Ltd.); aniline (Sinopharm Chemical Reagent Co., Ltd.); ammonium persulfate (Sinopharm Chemical Reagent Co., Ltd.); carbon dioxide (99.99% purity, Suzhou Jinhong Gas Co., Ltd.); argon (99.999% purity, Suzhou Jinhong Gas Co., Ltd.); nitrogen (99.999% purity, Suzhou Jinhong Gas Co., Ltd.).
[0019] The epoxy-functionalized polyaniline derivative (N-glycidylaniline-aniline copolymer) used in the following examples was synthesized as follows: Under nitrogen protection, N-glycidylaniline and aniline were dissolved in a 1 mol / L hydrochloric acid aqueous solution at a molar ratio of 1:9 (i.e., 10% molar percentage of N-glycidylaniline), resulting in a total monomer concentration of 0.1 mol / L. The solution was cooled to 0–5 °C. Ammonium persulfate was dissolved in a 1 mol / L hydrochloric acid solution at a molar ratio of 1:1 to the total monomer concentration. The ammonium persulfate solution was slowly added dropwise to the monomer solution with stirring over a period of 2 hours. After the addition was complete, the reaction was continued at 0–5 °C for 12 hours. After the reaction was completed, the reaction solution was filtered, and the precipitate was repeatedly washed with deionized water until the filtrate was colorless. The precipitate was then washed three times with acetone and dried under vacuum at 60 °C for 24 hours to obtain a dark green powder product, which was the copolymer with a 10% molar percentage of N-glycidylaniline. By adjusting the molar ratio of N-glycidyl aniline to aniline (5:95 to 15:85), copolymer products with a molar percentage of 5% and 15% of N-glycidyl aniline can be prepared respectively.
[0020] The composite sizing agent emulsion used in the following examples was prepared according to the following general method: Sulfonated cellulose nanocrystals were dispersed in deionized water and ultrasonically dispersed for 30 min (power 200W, frequency 40kHz) to obtain a cellulose nanocrystal dispersion. An epoxy-functionalized polyaniline derivative (N-glycidyl aniline-aniline copolymer) was dissolved in a small amount of N,N-dimethylformamide, and then slowly added to the cellulose nanocrystal dispersion under stirring. Stirring was continued for 30 min, and the mixture was diluted with deionized water to the desired solid content. The pH was adjusted to 6-7 to obtain the composite sizing agent emulsion. The mass ratio of cellulose nanocrystals to the epoxy-functionalized polyaniline derivative was adjusted according to the requirements of the specific examples.
[0021] Example 1
[0022] This embodiment provides a basalt fiber composite core overhead conductor and its manufacturing process, the specific steps of which are as follows: (1) Fiber preheating treatment: Place the continuous untwisted roving of basalt fiber (linear density 2400 tex, single filament diameter 13 μm) in a high temperature oven and heat treat it at 300℃ for 30 min to remove the original sizing agent and organic impurities on the fiber surface, and cool it to room temperature for later use.
[0023] (2) Preparation of composite sizing agent: Sulfonated cellulose nanofibers (diameter 5-10 nm, aspect ratio 10-20) and polyaniline derivatives with a molar percentage of 10% N-glycidyl aniline were prepared at a mass ratio of 1:5. Specifically, 1 g of sulfonated cellulose nanofibers were weighed and dispersed in 200 mL of deionized water, and ultrasonically dispersed for 30 min (power 200 W, frequency 40 kHz) to obtain a nanofiber cellulose whisker dispersion. 5 g of polyaniline derivatives with a molar percentage of 10% N-glycidyl aniline were weighed and dissolved in 20 mL of N,N-dimethylformamide. After stirring until completely dissolved, the solution was slowly added to the nanofiber cellulose whisker dispersion while stirring. Stirring was continued for 30 min. The solution was diluted with deionized water to a solid content of 2%, and the pH was adjusted to 6.5 with 0.1 mol / L ammonia water to obtain a composite sizing agent emulsion.
[0024] (3) Plasma pretreatment: The preheated basalt fiber is placed in a plasma treatment device, the vacuum is drawn to below 10Pa, argon gas is introduced to the chamber pressure to 50Pa, the gas flow rate is 100sccm, and plasma treatment is carried out at 200W power for 5min. After the treatment is completed, the fiber is taken out.
[0025] (4) Sizing agent coating: The plasma-pretreated basalt fibers are completely immersed in the composite sizing agent emulsion and treated at 25°C for 15 minutes. After removal, excess emulsion is removed by squeezing with a rubber roller and dried in an oven at 100°C for 30 minutes to obtain fiber bundles with modified coating.
[0026] (5) Resin matrix preparation: Take 100 parts by weight of bisphenol A type epoxy resin E51 (epoxy equivalent 185-210 g / eq) and heat to 60℃. Add 8 parts by weight of epoxidized polybutadiene rubber (epoxidation degree 35%, number average molecular weight 5000), and stir and disperse at 60℃ for 30 min (300 rpm) until the rubber is completely dissolved and evenly dispersed. Add 3 parts by weight of glycidyl POSS and continue stirring for 20 min. Add 80 parts by weight of methyltetrahydrophthalic anhydride curing agent and 2 parts by weight of 2-ethyl-4-methylimidazolium accelerator, stir and mix evenly, and then degas under vacuum at 60℃ for 20 min to obtain liquid resin matrix.
[0027] (6) Supercritical carbon dioxide-assisted impregnation and composite: The fiber bundle coated with the modified coating is placed in the high-pressure reactor of the supercritical fluid treatment device, and the prepared liquid resin matrix is injected into the reactor to impregnate the fiber bundle. The reactor is sealed, carbon dioxide is introduced to a predetermined pressure, and the temperature is heated to a predetermined temperature. The process is maintained in a supercritical state for a certain period of time to allow the resin to fully impregnate the fiber bundle. The specific process parameters are: temperature 60℃, pressure 12MPa, treatment time 30min, and supercritical carbon dioxide flow rate 20L / min. After the treatment is completed, the pressure is slowly released to atmospheric pressure, and the impregnated prepreg is removed.
[0028] (7) Non-isothermal gradient curing treatment: The prepreg was placed in a gradient curing oven and cured according to the following procedure: low temperature pre-curing stage, held at 100℃ for 60 min; heated to 150℃ at a heating rate of 3℃ / min, entering the medium temperature curing stage, held at 150℃ for 120 min; heated to 200℃ at a heating rate of 1℃ / min, entering the high temperature post-curing stage, held at 200℃ for 60 min. After curing, it was naturally cooled to room temperature to obtain a basalt fiber composite core (5 mm in diameter).
[0029] Example 2
[0030] The difference between this embodiment and Embodiment 1 lies in the resin matrix formulation, as detailed below: (1) Fiber preheating treatment: Same as step (1) in Example 1.
[0031] (2) Preparation of composite sizing agent: Same as step (2) in Example 1.
[0032] (3) Plasma pretreatment: Same as step (3) in Example 1.
[0033] (4) Coating with sizing agent: Same as step (4) in Example 1.
[0034] (5) Resin matrix preparation: Take 100 parts by weight of bisphenol F type epoxy resin NPEF-170 (epoxy equivalent 160~180g / eq) and heat to 55℃. Add 15 parts by weight of epoxidized polybutadiene rubber (epoxidation degree 50%, number average molecular weight 3000), and stir and disperse at 55℃ for 45min (speed 350rpm) until the rubber is completely dissolved and evenly dispersed. Add 5 parts by weight of glycidyl-based POSS and continue stirring for 25min. Add 35 parts by weight of 4,4′-diaminodiphenyl sulfone curing agent and 1.5 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol accelerator, stir and mix evenly, and then degas under vacuum at 55℃ for 25min to obtain liquid resin matrix.
[0035] (6) Supercritical carbon dioxide-assisted impregnation and composite: Same as step (6) in Example 1.
[0036] (7) Non-isothermal gradient curing treatment: Same as step (7) in Example 1.
[0037] Example 3
[0038] This embodiment comprehensively adopts the optimal fiber modification conditions, resin formulation, and curing process parameters, as detailed below: (1) Fiber preheating treatment: basalt fiber continuous untwisted roving (linear density 2400 tex, single filament diameter 13 μm) was placed in a high temperature oven and heat-treated at 350℃ for 45 min to remove the original sizing agent and organic impurities on the fiber surface, and then cooled to room temperature for use.
[0039] (2) Preparation of composite sizing agent: Sulfonated cellulose nanofibers (diameter 5-10 nm, aspect ratio 10-20) and polyaniline derivatives with a molar percentage of 10% N-glycidyl aniline were prepared at a mass ratio of 1:6. Specifically, 1 g of sulfonated cellulose nanofibers were weighed and dispersed in 250 mL of deionized water, and ultrasonically dispersed for 40 min (power 250 W, frequency 40 kHz) to obtain a nanofiber cellulose whisker dispersion. 6 g of polyaniline derivatives with a molar percentage of 10% N-glycidyl aniline were weighed and dissolved in 25 mL of N,N-dimethylformamide. After stirring until completely dissolved, the solution was slowly added to the nanofiber cellulose whisker dispersion while stirring. Stirring was continued for 40 min. The solution was diluted with deionized water to a solid content of 3%, and the pH was adjusted to 6.5 with 0.1 mol / L ammonia water to obtain a composite sizing agent emulsion.
[0040] (3) Plasma pretreatment: The preheated basalt fiber is placed in a plasma treatment device, the vacuum is drawn to below 10Pa, argon gas is introduced to the chamber pressure to 50Pa, the gas flow rate is 120sccm, and plasma treatment is carried out at 300W power for 8min. After the treatment is completed, the fiber is taken out.
[0041] (4) Sizing agent coating: The plasma-pretreated basalt fibers are completely immersed in the composite sizing agent emulsion and treated at 30°C for 20 minutes. After removal, excess emulsion is removed by squeezing with a rubber roller and dried in an oven at 110°C for 40 minutes to obtain fiber bundles with modified coating.
[0042] (5) Resin matrix preparation: Take 100 parts by weight of bisphenol A type epoxy resin E51 (epoxy equivalent 185-210 g / eq) and heat to 65℃. Add 12 parts by weight of epoxidized polybutadiene rubber (epoxidation degree 50%, number average molecular weight 3000), and stir and disperse at 65℃ for 40 min (speed 350 rpm) until the rubber is completely dissolved and evenly dispersed. Add 4 parts by weight of glycidyl POSS and continue stirring for 25 min. Add 85 parts by weight of methyltetrahydrophthalic anhydride curing agent and 2.5 parts by weight of 2-ethyl-4-methylimidazolium accelerator, stir and mix evenly, and then degas under vacuum at 65℃ for 25 min to obtain liquid resin matrix.
[0043] (6) Supercritical carbon dioxide-assisted impregnation and composite: The fiber bundle coated with the modified coating is placed in the high-pressure reactor of the supercritical fluid treatment device, and the prepared liquid resin matrix is injected into the reactor to impregnate the fiber bundle. The reactor is sealed, carbon dioxide is introduced to a predetermined pressure, and the temperature is heated to a predetermined temperature. The process is maintained in a supercritical state for a certain period of time to allow the resin to fully impregnate the fiber bundle. The specific process parameters are: temperature 65℃, pressure 13MPa, treatment time 40min, and supercritical carbon dioxide flow rate 25L / min. After the treatment is completed, the pressure is slowly released to atmospheric pressure, and the impregnated prepreg is removed.
[0044] (7) Non-isothermal gradient curing treatment: The prepreg was placed in a gradient curing oven and cured according to the following procedure: low temperature pre-curing stage, held at 110℃ for 90 min; heated to 160℃ at a heating rate of 2℃ / min, entering the medium temperature curing stage, held at 160℃ for 150 min; heated to 200℃ at a heating rate of 1℃ / min, entering the high temperature post-curing stage, held at 200℃ for 60 min. After curing, it was naturally cooled to room temperature to obtain a basalt fiber composite core (5 mm in diameter).
[0045] Example 4
[0046] The difference between this embodiment and Embodiment 3 is that the mass ratio of nanocellulose whiskers to polyaniline derivatives with epoxy functional groups in the composite sizing agent is 1:3, as detailed below: (1) Fiber preheating treatment: Same as step (1) in Example 3.
[0047] (2) Preparation of composite sizing agent: Sulfonated cellulose nanofibers (diameter 5-10 nm, aspect ratio 10-20) and polyaniline derivatives with a molar percentage of 10% N-glycidyl aniline were prepared at a mass ratio of 1:3. Specifically, 1 g of sulfonated cellulose nanofibers were weighed and dispersed in 150 mL of deionized water, and ultrasonically dispersed for 30 min (power 200 W, frequency 40 kHz) to obtain a nanofiber cellulose whisker dispersion. 3 g of polyaniline derivatives with a molar percentage of 10% N-glycidyl aniline were weighed and dissolved in 15 mL of N,N-dimethylformamide. After stirring until completely dissolved, the solution was slowly added to the nanofiber cellulose whisker dispersion while stirring. Stirring was continued for 30 min. The solution was diluted with deionized water to a solid content of 2.5%, and the pH was adjusted to 6.5 with 0.1 mol / L ammonia water to obtain a composite sizing agent emulsion.
[0048] (3) Plasma pretreatment: Same as step (3) in Example 3.
[0049] (4) Applying sizing agent: Same as step (4) in Example 3.
[0050] (5) Preparation of resin matrix: Same as step (5) in Example 3.
[0051] (6) Supercritical carbon dioxide-assisted impregnation and composite: Same as step (6) in Example 3.
[0052] (7) Non-isothermal gradient curing treatment: Same as step (7) in Example 3.
[0053] Example 5
[0054] The difference between this embodiment and Embodiment 3 is that the mass ratio of nanocellulose whiskers to polyaniline derivatives with epoxy functional groups in the composite sizing agent is 1:8, as detailed below: (1) Fiber preheating treatment: Same as step (1) in Example 3.
[0055] (2) Preparation of composite sizing agent: Sulfonated cellulose nanofibers (diameter 5-10 nm, aspect ratio 10-20) and polyaniline derivatives with a molar percentage of 10% N-glycidyl aniline were prepared at a mass ratio of 1:8. Specifically, 1 g of sulfonated cellulose nanofibers were weighed and dispersed in 350 mL of deionized water, and ultrasonically dispersed for 40 min (power 250 W, frequency 40 kHz) to obtain a nanofiber cellulose whisker dispersion. 8 g of polyaniline derivatives with a molar percentage of 10% N-glycidyl aniline were weighed and dissolved in 35 mL of N,N-dimethylformamide. After stirring until completely dissolved, the solution was slowly added to the nanofiber cellulose whisker dispersion while stirring. Stirring was continued for 40 min. The solution was diluted with deionized water to a solid content of 3.5%, and the pH was adjusted to 6.5 with 0.1 mol / L ammonia water to obtain a composite sizing agent emulsion.
[0056] (3) Plasma pretreatment: Same as step (3) in Example 3.
[0057] (4) Applying sizing agent: Same as step (4) in Example 3.
[0058] (5) Preparation of resin matrix: Same as step (5) in Example 3.
[0059] (6) Supercritical carbon dioxide-assisted impregnation and composite: Same as step (6) in Example 3.
[0060] (7) Non-isothermal gradient curing treatment: Same as step (7) in Example 3.
[0061] Example 6
[0062] The difference between this embodiment and Embodiment 3 is that the mass fraction of epoxidized polybutadiene rubber in the resin matrix is 5% (i.e., 100 parts by mass of base epoxy resin and 5 parts by mass of rubber), as detailed below: (1) Fiber preheating treatment: Same as step (1) in Example 3.
[0063] (2) Preparation of composite sizing agent: Same as step (2) in Example 3.
[0064] (3) Plasma pretreatment: Same as step (3) in Example 3.
[0065] (4) Applying sizing agent: Same as step (4) in Example 3.
[0066] (5) Resin matrix preparation: Take 100 parts by weight of bisphenol A type epoxy resin E51 (epoxy equivalent 185-210 g / eq) and heat to 65℃. Add 5 parts by weight of epoxidized polybutadiene rubber (epoxidation degree 50%, number average molecular weight 3000), and stir and disperse at 65℃ for 40 min (350 rpm) until the rubber is completely dissolved and evenly dispersed. Add 4 parts by weight of glycidyl POSS and continue stirring for 25 min. Add 85 parts by weight of methyltetrahydrophthalic anhydride curing agent and 2.5 parts by weight of 2-ethyl-4-methylimidazolium accelerator, stir and mix evenly, and then degas under vacuum at 65℃ for 25 min to obtain liquid resin matrix.
[0067] (6) Supercritical carbon dioxide-assisted impregnation and composite: Same as step (6) in Example 3.
[0068] (7) Non-isothermal gradient curing treatment: Same as step (7) in Example 3.
[0069] Example 7
[0070] The difference between this embodiment and Embodiment 3 is that the mass fraction of epoxidized polybutadiene rubber in the resin matrix is 20% (i.e., 100 parts by mass of base epoxy resin and 20 parts by mass of rubber), as detailed below: (1) Fiber preheating treatment: Same as step (1) in Example 3.
[0071] (2) Preparation of composite sizing agent: Same as step (2) in Example 3.
[0072] (3) Plasma pretreatment: Same as step (3) in Example 3.
[0073] (4) Applying sizing agent: Same as step (4) in Example 3.
[0074] (5) Resin matrix preparation: Take 100 parts by weight of bisphenol A type epoxy resin E51 (epoxy equivalent 185-210 g / eq) and heat to 65℃. Add 20 parts by weight of epoxidized polybutadiene rubber (epoxidation degree 50%, number average molecular weight 3000), and stir and disperse at 65℃ for 50 min (speed 350 rpm) until the rubber is completely dissolved and evenly dispersed. Add 4 parts by weight of glycidyl POSS and continue stirring for 25 min. Add 85 parts by weight of methyltetrahydrophthalic anhydride curing agent and 2.5 parts by weight of 2-ethyl-4-methylimidazolium accelerator, stir and mix evenly, and then degas under vacuum at 65℃ for 25 min to obtain liquid resin matrix.
[0075] (6) Supercritical carbon dioxide-assisted impregnation and composite: Same as step (6) in Example 3.
[0076] (7) Non-isothermal gradient curing treatment: Same as step (7) in Example 3.
[0077] Example 8
[0078] The difference between this embodiment and Embodiment 3 is that the mass fraction of glycidyl POSS in the resin matrix is 1% (i.e., 100 parts by mass of base epoxy resin and 1 part by mass of POSS), as detailed below: (1) Fiber preheating treatment: Same as step (1) in Example 3.
[0079] (2) Preparation of composite sizing agent: Same as step (2) in Example 3.
[0080] (3) Plasma pretreatment: Same as step (3) in Example 3.
[0081] (4) Applying sizing agent: Same as step (4) in Example 3.
[0082] (5) Resin matrix preparation: Take 100 parts by weight of bisphenol A type epoxy resin E51 (epoxy equivalent 185-210 g / eq) and heat to 65℃. Add 12 parts by weight of epoxidized polybutadiene rubber (epoxidation degree 50%, number average molecular weight 3000), and stir and disperse at 65℃ for 40 min (speed 350 rpm) until the rubber is completely dissolved and evenly dispersed. Add 1 part by weight of glycidyl POSS and continue stirring for 25 min. Add 85 parts by weight of methyltetrahydrophthalic anhydride curing agent and 2.5 parts by weight of 2-ethyl-4-methylimidazolium accelerator, stir and mix evenly, and then degas under vacuum at 65℃ for 25 min to obtain liquid resin matrix.
[0083] (6) Supercritical carbon dioxide-assisted impregnation and composite: Same as step (6) in Example 3.
[0084] (7) Non-isothermal gradient curing treatment: Same as step (7) in Example 3.
[0085] Example 9
[0086] The difference between this embodiment and Embodiment 3 is that the mass fraction of glycidyl POSS in the resin matrix is 8% (i.e., 100 parts by mass of base epoxy resin and 8 parts by mass of POSS), as detailed below: (1) Fiber preheating treatment: Same as step (1) in Example 3.
[0087] (2) Preparation of composite sizing agent: Same as step (2) in Example 3.
[0088] (3) Plasma pretreatment: Same as step (3) in Example 3.
[0089] (4) Applying sizing agent: Same as step (4) in Example 3.
[0090] (5) Resin matrix preparation: Take 100 parts by weight of bisphenol A type epoxy resin E51 (epoxy equivalent 185-210 g / eq) and heat to 65℃. Add 12 parts by weight of epoxidized polybutadiene rubber (epoxidation degree 50%, number average molecular weight 3000), and stir and disperse at 65℃ for 40 min (speed 350 rpm) until the rubber is completely dissolved and evenly dispersed. Add 8 parts by weight of glycidyl POSS and continue stirring for 30 min. Add 85 parts by weight of methyltetrahydrophthalic anhydride curing agent and 2.5 parts by weight of 2-ethyl-4-methylimidazolium accelerator, stir and mix evenly, and then vacuum degas at 65℃ for 25 min to obtain liquid resin matrix.
[0091] (6) Supercritical carbon dioxide-assisted impregnation and composite: Same as step (6) in Example 3.
[0092] (7) Non-isothermal gradient curing treatment: Same as step (7) in Example 3.
[0093] Comparative Example 1 (Unmodified Fiber) This comparative example uses basalt fiber raw yarn without any surface modification treatment, and the rest of the process is the same as in Example 3.
[0094] (1) Fiber preparation: Continuous untwisted roving of basalt fiber (linear density 2400 tex, single filament diameter 13 μm) is used directly without any preheating treatment, plasma treatment and sizing agent coating.
[0095] (2) Preparation of resin matrix: Same as step (5) in Example 3.
[0096] (3) Resin impregnation and lamination: Same as step (6) in Example 3.
[0097] (4) Non-isothermal gradient curing treatment: Same as step (7) in Example 3.
[0098] Comparative Example 2 (Treatment with conventional coupling agent) This comparative example uses the traditional silane coupling agent KH550 to treat the surface of basalt fibers, without plasma pretreatment and composite sizing agent coating. The remaining processes are the same as in Example 3.
[0099] (1) Fiber preheating treatment: Same as step (1) in Example 3.
[0100] (2) Coupling agent treatment: The preheated basalt fiber was immersed in a 2wt% KH550 silane coupling agent ethanol solution, soaked at 25℃ for 30min, and then dried at 110℃ for 60min.
[0101] (3) Preparation of resin matrix: Same as step (5) in Example 3.
[0102] (4) Resin impregnation and lamination: Same as step (6) in Example 3.
[0103] (5) Non-isothermal gradient curing treatment: Same as step (7) in Example 3.
[0104] Comparative Example 3 (conventional resin formulation, without toughening or reinforcement) This comparative example uses a pure epoxy resin system without added toughening agents and nano-reinforcing particles. The fibers undergo the same modification treatment as in Example 3, and the remaining processes are the same as in Example 3.
[0105] (1) Fiber preheating treatment: Same as step (1) in Example 3.
[0106] (2) Preparation of composite sizing agent: Same as step (2) in Example 3.
[0107] (3) Plasma pretreatment: Same as step (3) in Example 3.
[0108] (4) Applying sizing agent: Same as step (4) in Example 3.
[0109] (5) Resin matrix preparation: Take 100 parts by weight of bisphenol A type epoxy resin E51 (epoxy equivalent 185~210g / eq) and heat to 65℃. Add 85 parts by weight of methyltetrahydrophthalic anhydride curing agent and 2.5 parts by weight of 2-ethyl-4-methylimidazolium accelerator, stir and mix evenly, and then degas under vacuum at 65℃ for 25min to obtain liquid resin matrix (without adding epoxidized polybutadiene rubber and glycidyl-based POSS).
[0110] (6) Supercritical carbon dioxide-assisted impregnation and composite: Same as step (6) in Example 3.
[0111] (7) Non-isothermal gradient curing treatment: Same as step (7) in Example 3.
[0112] Comparative Example 4 (Rubber toughening only, no POSS reinforcement) In this comparative example, only epoxidized polybutadiene rubber was added to the resin matrix without the addition of POSS nanoparticles; otherwise, it was the same as in Example 3.
[0113] (1) Fiber preheating treatment: Same as step (1) in Example 3.
[0114] (2) Preparation of composite sizing agent: Same as step (2) in Example 3.
[0115] (3) Plasma pretreatment: Same as step (3) in Example 3.
[0116] (4) Applying sizing agent: Same as step (4) in Example 3.
[0117] (5) Resin matrix preparation: Take 100 parts by weight of bisphenol A type epoxy resin E51 (epoxy equivalent 185-210 g / eq) and heat to 65℃. Add 12 parts by weight of epoxidized polybutadiene rubber (epoxidation degree 50%, number average molecular weight 3000), and stir and disperse at 65℃ for 40 min (speed 350 rpm) until the rubber is completely dissolved and evenly dispersed. Add 85 parts by weight of methyltetrahydrophthalic anhydride curing agent and 2.5 parts by weight of 2-ethyl-4-methylimidazolium accelerator, stir and mix evenly, and then degas under vacuum at 65℃ for 25 min to obtain liquid resin matrix (without adding glycidyl-based POSS).
[0118] (6) Supercritical carbon dioxide-assisted impregnation and composite: Same as step (6) in Example 3.
[0119] (7) Non-isothermal gradient curing treatment: Same as step (7) in Example 3.
[0120] Comparative Example 5 (POSS reinforcement only, no rubber toughening) In this comparative example, only POSS nanoparticles were added to the resin matrix without epoxidized polybutadiene rubber; otherwise, it was the same as in Example 3.
[0121] (1) Fiber preheating treatment: Same as step (1) in Example 3.
[0122] (2) Preparation of composite sizing agent: Same as step (2) in Example 3.
[0123] (3) Plasma pretreatment: Same as step (3) in Example 3.
[0124] (4) Applying sizing agent: Same as step (4) in Example 3.
[0125] (5) Resin matrix preparation: Take 100 parts by weight of bisphenol A type epoxy resin E51 (epoxy equivalent 185~210g / eq) and heat to 65℃. Add 4 parts by weight of glycidyl-based POSS and stir at 65℃ for 25min. Add 85 parts by weight of methyltetrahydrophthalic anhydride curing agent and 2.5 parts by weight of 2-ethyl-4-methylimidazolium accelerator, stir and mix evenly, and then vacuum degas at 65℃ for 25min to obtain liquid resin matrix (without adding epoxidized polybutadiene rubber).
[0126] (6) Supercritical carbon dioxide-assisted impregnation and composite: Same as step (6) in Example 3.
[0127] (7) Non-isothermal gradient curing treatment: Same as step (7) in Example 3.
[0128] Comparative Example 6 (Conventional impregnation process, non-supercritical auxiliary) This comparative example uses a conventional atmospheric pressure impregnation process instead of supercritical carbon dioxide-assisted impregnation, and the rest is the same as in Example 3.
[0129] (1) Fiber preheating treatment: Same as step (1) in Example 3.
[0130] (2) Preparation of composite sizing agent: Same as step (2) in Example 3.
[0131] (3) Plasma pretreatment: Same as step (3) in Example 3.
[0132] (4) Applying sizing agent: Same as step (4) in Example 3.
[0133] (5) Preparation of resin matrix: Same as step (5) in Example 3.
[0134] (6) Conventional atmospheric pressure impregnation and lamination: The fiber bundle coated with the modified coating is completely immersed in the prepared liquid resin matrix and impregnated at 65°C and atmospheric pressure for 120 minutes, with stirring every 15 minutes to ensure uniform impregnation. After removal, excess resin is squeezed out with a rubber roller to obtain the prepreg.
[0135] (7) Non-isothermal gradient curing treatment: Same as step (7) in Example 3.
[0136] Comparative Example 7 (Conventional curing process, non-gradient curing) This comparative example uses a conventional isothermal curing process instead of non-isothermal gradient curing, and the rest is the same as in Example 3.
[0137] (1) Fiber preheating treatment: Same as step (1) in Example 3.
[0138] (2) Preparation of composite sizing agent: Same as step (2) in Example 3.
[0139] (3) Plasma pretreatment: Same as step (3) in Example 3.
[0140] (4) Applying sizing agent: Same as step (4) in Example 3.
[0141] (5) Preparation of resin matrix: Same as step (5) in Example 3.
[0142] (6) Supercritical carbon dioxide-assisted impregnation and composite: Same as step (6) in Example 3.
[0143] (7) Conventional isothermal curing treatment: The prepreg is placed in an oven and cured at 160°C for 240 min. After curing, it is naturally cooled to room temperature to obtain a basalt fiber composite core (5 mm in diameter).
[0144] The following methods were used to perform performance tests on all embodiments and comparative examples: Tensile strength test: The test was conducted according to GB / T 3354-2014 "Test Method for Tensile Properties of Directed Fiber Reinforced Polymer Matrix Composites". The specific steps are as follows: The composite core specimen was processed into standard dimensions (200 mm in length, 150 mm in gauge length, and 5 mm in diameter), and both ends were protected with aluminum reinforcing plates. A universal testing machine was used for the tensile test, with a loading rate of 2 mm / min. The tensile strength was calculated using the following formula: σ t = F max / A, where F max The maximum tensile load is (N), and A is the initial cross-sectional area of the specimen (mm²). 2 Five parallel samples were tested for each group of samples, and the average value was taken.
[0145] Flexural modulus test: The test was conducted according to GB / T 1449-2005 "Test Method for Flexural Properties of Fiber Reinforced Plastics". The specific steps are as follows: The composite core sample was processed into a 100mm long, 5mm diameter round bar. A three-point bending loading method was used, with a span of 80mm, a pressure head radius of 5mm, and a support radius of 5mm. The loading rate was 2mm / min, and the load-deflection curve was recorded. The flexural modulus was calculated using the following formula: E f = (L 3 × ΔF) / (4 × b × h 3 For a circular cross-section specimen, b and h are both taken as the diameter d, and the formula simplifies to E. f = (L 3 × ΔF) / (4 × d 4 × Δδ), where L is the span (mm), ΔF is the load increment (N) of the linear segment of the load-deflection curve, d is the specimen diameter (mm), and Δδ is the corresponding deflection increment (mm). Five parallel samples are tested for each group of specimens, and the average value is taken.
[0146] Fracture toughness (K) IC Test: The test was conducted according to ASTM D5045-14. The specific steps are as follows: The composite core specimen was processed into a compact tensile (CT) specimen with a thickness B = 5 mm, a width W = 20 mm, and a pre-crack length a ≈ 10 mm (a / W ≈ 0.5). Loading was performed on a universal testing machine at a loading rate of 1 mm / min, and the maximum load P was recorded. max Fracture toughness is calculated using the following formula: K IC = (P max / (B × W 1 / 2 )) × f(a / W), where f(a / W) is the geometric factor. For CT specimens, f(a / W) = ((2 + a / W) / (1 - a / W) 3 / 2 ) × (0.886 + 4.64(a / W) - 13.32(a / W) 2 +14.72 (a / W) 3 - 5.6 (a / w) 4 Five parallel samples were tested for each group of samples, and the average value was taken.
[0147] Interfacial shear strength (IFSS) test: Short beam shear tests are performed according to ASTM D2344 / D2344M-16. The short beam shear strength indirectly reflects the interfacial bond strength. The specific steps are as follows: The composite core sample is processed into a short rod with a length of 30 mm and a diameter of 5 mm. A three-point bending load is applied with a span of 20 mm (span-to-thickness ratio 4:1) at a loading rate of 1 mm / min. The maximum load P_max is recorded. The short beam shear strength is calculated using the following formula: τ = 0.75 × P max / (b × h), for a circular cross-section, where b and h are both taken as the diameter d, the formula simplifies to τ = 0.75 × P max / d 2 Five parallel samples were tested for each group of samples, and the average value was taken.
[0148] Porosity testing: The test was conducted according to GB / T 3365-2008 "Test Methods for Pore Content and Fiber Volume Content of Carbon Fiber Reinforced Plastics". The specific steps are as follows: Cut approximately 2g of sample from the composite core and accurately weigh the mass m1 of the sample in air (accurate to 0.1mg). Place the sample in a beaker and add sufficient amount of impregnation liquid with a known density (using anhydrous ethanol, density ρ). l =0.789g / cm 3 The vacuum is evacuated to below -0.095 MPa and maintained for 30 minutes to allow the impregnation solution to fully fill the internal pores of the sample. The sample is then removed, and excess liquid is gently absorbed with filter paper. The mass (m2) of the sample in air after impregnation is measured. The impregnated sample is then suspended in the impregnation solution, and its mass (m3) in the solution is measured (accurate to 0.1 mg). Porosity is calculated using the following formula: V v = (m2 - m1) / (m2 - m3) × 100%, where V v Porosity (%). Five parallel samples were tested for each group of samples, and the average value was taken.
[0149] Fiber volume fraction test: The test was conducted according to GB / T 3365-2008 "Test Method for Pore Content and Fiber Volume Content of Carbon Fiber Reinforced Plastics". The specific steps are as follows: Cut approximately 2g of sample from the composite core and accurately weigh the sample mass m0 (accurate to 0.1mg). Place the sample in a muffle furnace and ignite at 600℃ for 4 hours to completely burn off the resin matrix. After cooling, weigh the remaining fiber mass m. f The fiber volume fraction is calculated using the following formula: V f = (m f / ρ f ) / (m0 / ρ c ), where ρ_f is the density of basalt fibers (taken as 2.65 g / cm³). 3 ), ρc The measured density of the composite core (determined by the water displacement method) is given. Five parallel samples were tested for each group of specimens, and the average value was taken.
[0150] Tensile strength retention rate test after damp heat aging: Damp heat aging treatment was performed according to GB / T 2573-2008 "Test Method for Damp Heat of Glass Fiber Reinforced Plastics". The specific steps are as follows: The composite core sample was placed in a constant temperature and humidity chamber and aged for 1000 hours at 70℃ and 95% relative humidity. After aging, the sample was removed and placed at room temperature for 24 hours before tensile strength testing, using the same method as in Section 6.1. The tensile strength retention rate was calculated using the following formula: R = σ aged / σ initial ×100%, where σ aged Tensile strength (MPa) after damp heat aging, σ initial The initial tensile strength (MPa) of the unaged specimen. Five parallel samples were tested in each group, and the average value was taken.
[0151] Comparing Example 3 with Comparative Example 1, the decisive influence of fiber surface modification on the composite material's properties is clearly evident. The tensile strength of Example 3 increased by 97.6% compared to Comparative Example 1, the interfacial shear strength increased by 96.9%, and the fracture toughness increased by 147.6%. The fundamental reason for this significant improvement is that the unmodified basalt fiber surface is smooth and chemically inert, exhibiting only weak van der Waals physical bonding with the resin matrix. Load cannot be effectively transferred from the matrix to the fiber reinforcement, and the composite material's failure mode is primarily interfacial debonding. In contrast, this invention uses a composite sizing agent of nanocellulose whiskers and epoxy-functionalized polyaniline derivatives to modify the fiber surface, forming a multifunctional modified coating. Specifically, the nanocellulose whiskers construct a nanoscale rough structure on the fiber surface, increasing the mechanical interlocking and physical anchoring effect between the fiber and the matrix. Simultaneously, the abundant hydroxyl functional groups on the surface of the nanocellulose whiskers can form hydrogen bonds with the silanol groups on the basalt fiber surface, firmly adhering to the fiber surface. More importantly, the polyaniline derivative with epoxy functional groups can interact with the active sites on the surface of basalt fibers through its benzene ring structure via π-π interactions. Furthermore, the epoxy functional groups introduced into its molecular chain can copolymerize with epoxy groups in the resin matrix or the curing agent during subsequent curing, forming chemical bonds. This synergistic effect of physical anchoring and chemical bonding establishes an efficient load transfer channel between the fiber and the matrix, resulting in a nearly 100% increase in interfacial shear strength. Although the interfacial shear strength of Comparative Example 2 is improved compared to the unmodified fiber, it is still far lower than the level of the embodiments of this invention, indicating that traditional coupling agents can only introduce limited reactive functional groups onto the fiber surface and cannot achieve the dual synergistic effect of physical anchoring of nanocellulose whiskers and chemical bonding of polyaniline derivatives as described in this invention.
[0152] By comparing Example 3 with Comparative Examples 3, 4, and 5, the synergistic mechanism of the toughening and reinforcing components in the resin matrix can be systematically analyzed. Comparative Example 3 uses a pure epoxy resin system. Although the interfacial bonding is good, the fracture toughness, tensile strength, and flexural modulus are not ideal due to the inherent high crosslinking density and brittleness of the cured epoxy resin. This indicates that the brittleness of the pure epoxy resin matrix itself is a bottleneck restricting the overall performance of the composite material. Comparative Example 4 adds only epoxidized polybutadiene rubber toughening agent without POSS, resulting in a significant increase in fracture toughness and tensile strength, but the flexural modulus only increases by 5.1% compared to the pure epoxy system. This shows that rubber toughening can indeed effectively improve the fracture toughness of the material. Its toughening mechanism lies in the rubber phase forming a micron-sized dispersed phase in the resin matrix, inducing shear yielding and creasing in the matrix under stress, thereby absorbing a large amount of fracture energy. However, the introduction of the rubber phase also brings the problem of modulus loss: rubber itself is a low-modulus soft segment, and its dispersion in the rigid epoxy network is equivalent to introducing a mechanical weak point, making the improvement in the flexural modulus of the composite material extremely limited. Comparative Example 5, which only added glycidyl-based POSS without adding a rubber toughening agent, showed a 24.1% increase in flexural modulus and a 48.0% increase in tensile strength compared to the pure epoxy system, but an 87.5% increase in fracture toughness. This demonstrates that POSS nanoparticles can indeed effectively reinforce the resin matrix. POSS is a nanoparticle with a rigid Si-O inorganic cage-like framework. Its nanoscale size ensures uniform dispersion in the resin matrix, and its surface epoxy functional groups can participate in the formation of the resin cross-linking network, allowing POSS to be chemically bonded into the cross-linking network, thereby significantly improving the modulus and strength of the matrix. However, the rigid nature of POSS determines its limited toughening effect; using POSS alone cannot solve the brittleness problem of epoxy resin. Example 3, with the simultaneous addition of epoxidized polybutadiene rubber and glycidyl-based POSS, exhibited remarkable synergistic effects: fracture toughness increased by 201.3% compared to the pure epoxy system, 19.0% compared to rubber-only toughening, and 60.7% compared to POSS-only reinforcement; flexural modulus increased by 29.2% compared to the pure epoxy system, 22.9% compared to rubber-only toughening; and tensile strength increased by 71.4% compared to the pure epoxy system. The mechanism of this synergistic effect can likely be explained by the formation of a complementary toughening and reinforcing network between the rubber phase and POSS within the epoxy matrix. The rubber phase provides the primary energy dissipation pathway through induced shear yielding and crimping, while the POSS nanoparticles compensate for the modulus loss caused by the rubber phase through their rigid framework. Simultaneously, the epoxy functional groups on the POSS surface participate in the cross-linking network, further enhancing the cross-linking density and strength of the matrix. More importantly, the enrichment of POSS nanoparticles around the rubber phase can form a rigid shell around the rubber particles. This soft core and hard shell structure can effectively transfer and disperse stress, and limit the excessive deformation of the rubber phase, thus achieving a synergistic unity of toughening and strengthening.It is worth noting that the combined use of epoxidized polybutadiene rubber and POSS in this invention not only solves the long-standing technical problem of mutual constraints between toughening and heat resistance and modulus in the industry, but also the synergistic effect of the two is far greater than the simple sum of their individual effects.
[0153] As can be seen from Examples 6, 3, and 7, the fracture toughness continuously improves with increasing rubber content, but the flexural modulus first increases and then decreases, and the tensile strength also shows a trend of first increasing and then decreasing. This indicates that there is an optimal range of rubber addition: too low a rubber content results in insufficient toughening effect, while too high a rubber content leads to excessive soft segments that dilute the rigidity and strength of the matrix. Data from Examples 8, 3, and 9 show that the flexural modulus and tensile strength continuously improve with increasing POSS content, but the fracture toughness reaches its optimum at a POSS content of 4 parts by mass, and decreases when further increased to 8 parts by mass. This may be because excessive POSS nanoparticles agglomerate in the matrix, becoming stress concentration sources and brittleness initiation points. Therefore, the preferred rubber content range (5–20 parts by mass) and POSS content range (1–8 parts by mass) of this invention are the optimal parameter windows determined after comprehensively balancing various performance indicators.
[0154] By comparing Example 3 and Comparative Example 6, the effect of supercritical carbon dioxide-assisted impregnation on improving the porosity of the composite material can be analyzed. The porosity of Example 3 was only 0.35%, while that of Comparative Example 6 was as high as 2.85%, with the former being 87.7% lower than the latter. The fundamental reason for this significant difference lies in the unique physicochemical properties of supercritical carbon dioxide. Supercritical carbon dioxide, in its supercritical state, possesses both the high diffusivity of a gas and the high solubility of a liquid. Its viscosity is close to that of a gas, and its surface tension is close to zero, which allows supercritical carbon dioxide to easily penetrate into the narrow pores between the single filaments inside the fiber bundle, with widths ranging from nanometers to micrometers. During the penetration process, supercritical carbon dioxide carries the resin matrix into the fiber bundle. When the pressure is slowly released after the treatment, the carbon dioxide changes from the supercritical state to a gaseous state and escapes, while the resin remains in the pores inside the fiber bundle, completing the filling process. In contrast, in conventional atmospheric pressure impregnation processes, the high viscosity and surface tension of the liquid resin make it difficult for the resin to overcome capillary resistance and enter the micro-nano pores inside the fiber bundle. A large number of pores cannot be filled by the resin, becoming defects in the composite material. These pores not only become stress concentration sources during service, leading to a decline in mechanical properties, but also provide channels for the intrusion of environmental factors such as moisture and oxygen, accelerating the aging and failure of the material. The tensile strength retention rate after damp heat aging in Example 3 was significantly higher than that in Comparative Example 6, which indirectly confirms the important role of low porosity in improving the long-term durability of materials.
[0155] Comparing Example 3 with Comparative Example 7, the improvement effect of non-isothermal gradient curing on the composite material properties can be analyzed. Example 3 showed a significantly higher tensile strength retention rate and fracture toughness after wet heat aging compared to Comparative Example 7, while tensile strength and flexural modulus were also improved. This difference can be explained from two perspectives: curing reaction kinetics and internal stress regulation. The curing reaction of epoxy resin is an exothermic cross-linking polymerization reaction. In conventional isothermal curing, the entire sample is rapidly heated to a high temperature, and intense cross-linking reactions begin simultaneously on the surface and inside. The exothermic reaction further increases the internal temperature of the sample, resulting in a faster internal reaction rate than the surface, creating a non-uniform curing situation with slower external and faster internal processes. This non-uniform curing first leads to spatial non-uniformity of the cross-linking network structure: high internal cross-linking density and low surface cross-linking density, causing inhomogeneity in material properties. More seriously, the chemical shrinkage and thermal shrinkage during curing generate huge thermal and shrinkage stresses inside the sample. These internal stresses, combined with external stresses during material service, accelerate material damage and failure. The non-isothermal gradient curing process employed in this invention effectively solves the aforementioned problems through precise temperature control in three stages: the low-temperature pre-curing stage allows the resin system to slowly initiate the cross-linking reaction at a lower temperature, resulting in a low reaction rate, gradual exothermic reaction, and a uniform temperature field within the sample; the medium-temperature curing stage is the main cross-linking reaction stage, at which point the sample has established a relatively uniform initial cross-linking network through the pre-curing stage, and subsequent cross-linking reactions occur on this relatively uniform network; the high-temperature post-curing stage ensures that the resin system reaches sufficient cross-linking density and glass transition temperature. This staged, step-by-step curing regime effectively suppresses local overheating and uneven curing caused by exothermic reactions, resulting in a more uniform final cross-linking network structure. Simultaneously, the gradual process of pre-curing, curing, and post-curing allows internal stress to be released gradually rather than erupting all at once, ultimately yielding composite material products with good dimensional stability, low internal stress, and excellent overall performance. The results of the damp heat aging test are particularly convincing: in harsh environments of high temperature and high humidity, materials with high internal stress are more prone to initiating microcracks at stress concentration points, thereby accelerating moisture intrusion and performance degradation. The gradient-cured products of this invention, with their low internal stress, exhibit excellent aging resistance.
[0156] In summary, at the fiber level, this invention employs a composite sizing agent containing bio-based nanomaterials and functional polymers to reconstruct the fiber surface. The nanoscale effect of cellulose whiskers and the abundance of hydroxyl functional groups on their surface increase the physical anchor points and chemical bonding sites on the fiber surface. Simultaneously, a copolymerization reaction is achieved between a polyaniline derivative with epoxy functional groups and the epoxy groups in the resin matrix, establishing a chemical bridge between the fiber and the matrix, thereby forming a modulus gradient transition layer at the interface. At the matrix level, an epoxidized polybutadiene rubber phase and POSS nanoparticles are introduced for synergistic toughening and reinforcement. The rubber phase absorbs impact energy by inducing shear yielding and crimping in the matrix, while the POSS nanoparticles provide reinforcement through their rigid inorganic silica cage-like framework and compensate for the modulus loss caused by rubber toughening. Furthermore, the epoxy functional groups on the POSS surface can participate in the formation of the resin crosslinking network, achieving a synergistic unity of toughening and reinforcement. At the process level, the superior permeability, zero surface tension, and low viscosity of supercritical carbon dioxide are utilized to assist resin impregnation, enabling the resin to fully penetrate the surface of each monofilament within the fiber bundle. Simultaneously, a non-isothermal gradient curing regime is employed to precisely control the cross-linking reaction rate and degree of the resin in stages, effectively eliminating internal thermal and shrinkage stresses and ensuring the dimensional stability and mechanical reliability of the product. Through this synergistic innovation encompassing the fiber interface, resin matrix, and molding process, a comprehensive improvement in the performance of low-cost basalt fiber composite materials is achieved.
[0157] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
[0158] The present invention and its embodiments have been described above. This description is not restrictive, but merely one embodiment of the present invention, and the actual application is not limited thereto. In conclusion, if those skilled in the art are inspired by this description and design similar methods and embodiments without departing from the spirit of the present invention, they should all fall within the protection scope of the present invention.
Claims
1. A basalt fiber composite core overhead conductor, characterized in that, include: A fiber bundle consisting of multiple basalt fiber monofilaments, and a resin matrix impregnated and cured inside and on the surface of the fiber bundle; The surface of the basalt fiber monofilament has a modified coating, and the resin matrix is a modified thermosetting resin system that has been toughened and nano-reinforced.
2. The basalt fiber composite core overhead conductor according to claim 1, characterized in that, The modified coating is a composite sizing agent coating comprising nanocellulose whiskers and a conductive polymer derivative; the conductive polymer derivative is a polyaniline derivative with epoxy functional groups; the mass ratio of nanocellulose whiskers to the polyaniline derivative with epoxy functional groups in the composite sizing agent coating is 1:3 to 1:8; the nanocellulose whiskers are sulfonated cellulose nanowhiskers with a diameter of 5-10 nm and an aspect ratio of 10-20; the polyaniline derivative with epoxy functional groups is a copolymer of N-glycidyl aniline and aniline, wherein the molar percentage of N-glycidyl aniline is 5%-15%.
3. The basalt fiber composite core overhead conductor according to claim 1, characterized in that, The resin matrix comprises a base epoxy resin, a toughening modifier, and nano-reinforcing particles; the toughening modifier is a block copolymer rubber, and the nano-reinforcing particles are polyhedral oligomeric silsesquioxanes; the base epoxy resin is a bisphenol A type epoxy resin or a bisphenol F type epoxy resin, with an epoxy equivalent of 170–210 g / eq; the block copolymer rubber is an epoxidized polybutadiene rubber with an epoxidation degree of 20%–60%, a number average molecular weight of 2000–8000, and a mass fraction of 5%–20% in the resin matrix; the polyhedral oligomeric silsesquioxane is a polyhedral oligomeric silsesquioxane with epoxy groups, and a mass fraction of 1%–8% in the resin matrix; the mass ratio of the base epoxy resin, the epoxidized polybutadiene rubber, and the polyhedral oligomeric silsesquioxane in the resin matrix is 100:(5–20):(1–8).
4. The basalt fiber composite core overhead conductor according to claim 1, characterized in that, A gradient interface layer is formed between the fiber bundle and the resin matrix. The modulus of the gradient interface layer decreases from the inside to the outside along the radial direction of the fiber. The thickness of the gradient interface layer is 50–200 nm. The diameter of the basalt fiber monofilaments in the fiber bundle is 7–20 μm, the linear density of the fiber bundle is 600–4800 tex, and the number of monofilaments in the fiber bundle is 50–400.
5. The basalt fiber composite core overhead conductor according to claim 1, characterized in that, The composite core has a fiber volume fraction of 50%–75%, a resin matrix volume fraction of 25%–50%, and a diameter of 2–15 mm.
6. A manufacturing process for an overhead conductor with a basalt fiber composite core as described in any one of claims 1 to 5, characterized in that, Includes the following steps: Surface modification treatment of basalt fibers was carried out to obtain fiber bundles with modified coatings; The modified fiber bundles were impregnated with a liquid resin matrix under the assistance of supercritical fluid to obtain a prepreg; the prepreg was then subjected to a non-isothermal gradient curing treatment to obtain the composite material core.
7. The production process according to claim 6, characterized in that, The surface modification treatment includes plasma pretreatment and sizing agent coating; the plasma pretreatment atmosphere is argon or nitrogen, the treatment power is 100-500W, the treatment time is 1-10min, and the gas flow rate is 50-200sccm; the sizing agent coating uses a composite emulsion containing nano-cellulose whiskers and polyaniline derivatives with epoxy functional groups; the solid content of the composite emulsion is 1%-5%, and the mass ratio of nano-cellulose whiskers to polyaniline derivatives with epoxy functional groups is 1:3 to 1:8; the sizing agent coating is performed by immersion, the immersion time is 5-30min, the immersion temperature is 20-40℃, and after coating, it is dried at 80-120℃ for 10-60min.
8. The production process according to claim 6, characterized in that, The supercritical fluid is supercritical carbon dioxide; the impregnation and composite temperature is 40–80°C, the pressure is 8–15 MPa, and the processing time is 10–60 min; the flow rate of supercritical carbon dioxide is 5–50 L / min.
9. The production process according to claim 6, characterized in that, The non-isothermal gradient curing process includes a low-temperature pre-curing stage, a medium-temperature curing stage, and a high-temperature post-curing stage performed sequentially. The temperature of the low-temperature pre-curing stage is 80–120°C, and the time is 30–120 min. The temperature of the medium-temperature curing stage is 130–170°C, and the time is 60–180 min. The temperature of the high-temperature post-curing stage is 180–220°C, and the time is 30–90 min. The heating rate from the low-temperature pre-curing stage to the medium-temperature curing stage is 1–5°C / min, and the heating rate from the medium-temperature curing stage to the high-temperature post-curing stage is 0.5–3°C / min.
10. The production process according to claim 6, characterized in that, The resin matrix is pre-prepared before impregnation and lamination, specifically as follows: the base epoxy resin is heated to 50-80°C, epoxidized polybutadiene rubber is added and stirred and dispersed for 10-60 minutes, polyhedral oligomeric silsesquioxane is added and stirred for another 10-30 minutes, a curing agent and an accelerator are added, and the mixture is stirred and mixed evenly, followed by vacuum degassing for 10-30 minutes; the curing agent is an anhydride-based curing agent or an amine-based curing agent, and the amount of curing agent is 50%-100% of the mass of the epoxy resin. The accelerator is a tertiary amine accelerator or an imidazole accelerator, and the amount of accelerator is 0.5% to 5% of the epoxy resin mass; the anhydride curing agent is methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, or nadic anhydride; the amine curing agent is 4,4′-diaminodiphenylmethane, 4,4′-diaminodiphenyl sulfone, or m-phenylenediamine; the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol, N,N-dimethylbenzylamine, or 2-ethyl-4-methylimidazole.